Role of a cyclooxygenase-2 cascade in breast cancer cell dissemination - M. A. Taipov; I. A. Kudryavtsev; K. P. Laktionov; N. E. Levchenko; V. E. Shevchenko (ABV-press, 2014)
Current therapeutic approaches based on a study of the genetic portrait of a tumor individualize treatment policy to a greater extent, which cre- ates real prospects for the increasing number of patients to recover. Experimental and clinical evidence suggest that the increased expression of the COX-2 gene increases the risk for breast cancer (BC) cell dissemination into distant organs. A number of recent studies have revealed that selec- tive COX-2 inhibitors are able to suppress proliferation, to induce apoptosis in the BC cells, and to inhibit tumor neoangiogenesis. However, this area contains many unclear and disputable problems to be still experimentally solved. Our review deals with the theoretical prerequisites for and the analysis of a role of COX-2 in BC cell dissemination.